« Dans le même temps, je découvre que je suis blanche… ». Entretien avec Christelle Hamel - Christelle Hamel; Isabelle Clair (Genre, Sexualité et Société)
Christelle Hamel has been in charge of research at l’Institut National d’Études Démographiques (INED) [National Institute of Demographic Studies] since 2006. She is part of the research group who designed the quantitative inquiry « Trajectories and Origins » (TeO), the initial results of which have begun to be published (http://teo.site.ined.fr/fr). In this interview, conducted in November of 2011, Christelle Hamel reflects on earlier research conducted as part of her doctoral dissertation in anthropology regarding « the managementofHIV infection risk by youngFrenchdescendants ofmigrants from the Maghreb”. She recounts the successive discoveries that marked her inquiry conducted in the 1990’s, the obstacles she encountered, the methodological and theoretical detours she had to take to overcome them, and finally the readings that guided her to unearth “the entanglement of social relations marked by sex, race, age, and class” in the emotional and sexual lives of the people she interviewed.